2021
DOI: 10.3390/polym13244302
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Evaluation of Chitosan/NaCl/Maltodextrin Microparticles as a Saltiness Enhancer: Study on the Optimization of Excipients for the Spray-Drying Process

Abstract: Spray-dried chitosan/NaCl/maltodextrin microparticles have the potential to be used to enhance saltiness; however, its notable hygroscopicity results in handling and storage problems, thus limiting its application. In the present study, we attempted to introduce maltodextrin, microcrystalline cellulose (MCC), and waxy starch (WS) as excipients into the spray drying formulation of microparticles to reduce the cohesiveness and caking behavior and improve the yield simultaneously by ameliorating the moisture abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Regarding the maltodextrin coating, it exhibited the lowest water content among treatments. Elevated maltodextrin ratios led to the formation of amorphous structures and reduced water content, likely due to diminished hygroscopicity (Wang et al., 2021 ) and decreased hydrophilicity. Dextrins, with their fundamental 1,6‐glycosidic and 1,4‐glycosidic linkages, are known for their substantial water‐binding properties (Włodarczyk & Śliżewska, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the maltodextrin coating, it exhibited the lowest water content among treatments. Elevated maltodextrin ratios led to the formation of amorphous structures and reduced water content, likely due to diminished hygroscopicity (Wang et al., 2021 ) and decreased hydrophilicity. Dextrins, with their fundamental 1,6‐glycosidic and 1,4‐glycosidic linkages, are known for their substantial water‐binding properties (Włodarczyk & Śliżewska, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, in the ethanol extract of dragon fruit peel powder, the treatment with the lowest change was the maltodextrin application treatment, with a change of 22.09%.Regarding the maltodextrin coating, it exhibited the lowest water content among treatments. Elevated maltodextrin ratios led to the formation of amorphous structures and reduced water content, likely due to diminished hygroscopicity(Wang et al, 2021) and decreased hydrophilicity. Dextrins, with their fundamental 1,6-glycosidic and 1,4-glycosidic linkages, are known for their substantial water-binding…”
mentioning
confidence: 99%
“…The decrease in moisture content is one of the factors that can decrease the salinity of fermented sausages ( Tian et al, 2020 ). When NaCl dissolves in water to dissociate into Na + and Cl − , the migration of Na + through the ion channels elicits depolarization, causing saltiness ( Wang et al, 2021 ). The intense saltiness across the treatment groups is, thus, presumed to have arisen from the lower content of water than that in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, Wang et al prepared spray-dried chitosan/NaCl/ maltodextrin particles, achieving a 25% reduction in sodium content without compromising flavor. 152 However, certain studies have indicated that the use of large-grain size salt can enhance the perception of saltiness. The late addition of coarse-grained salt with a size of 0.4-1.4 mm in the pizza crust results in a faster release of sodium and a stronger salty sensation.…”
Section: Salt Particle Structure Engineeringmentioning
confidence: 99%
“…Consequently, Wang et al prepared spray-dried chitosan/NaCl/maltodextrin particles, achieving a 25% reduction in sodium content without compromising flavor. 152…”
Section: Salt Reduction Strategies Of Foodmentioning
confidence: 99%